2021
DOI: 10.1155/2021/6648455
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Shenmayizhi Decoction Ameliorates Memory and Cognitive Impairment Induced by Multiple Cerebral Infarctions

Abstract: This study aimed to illustrate the mechanism by which Shenmayizhi decoction (SMYZD) improves the learning memory of rats with vascular cognitive impairment (VCI). Fifty male and female Wistar rats of specific pathogen-free grade (SPF grade) were used to establish the model by the administration of a microsphere embolization. This was accomplished by injecting sterile, standardized, mass-produced microspheres of uniform particle size (100–200 µm in diameter) in a sodium alginate microsphere vascular embolic age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Researchers also showed that YZQXF ameliorated cognitive decline by decreasing BDNF, TrkB, TNFα, IL-2, and IL-6 levels and upregulating acetylcholine and IL-10, thus promoting the activation of Erk and Akt signaling in APP/PS1 mice [23]. In an in vivo model of AD, SMYZD at concentrations of 11.88 g/kg/d can significantly improve memory abilities associated with an increase in the levels of NG2 and Ang1 protein expression levels in Wistar rats [22]. An in vitro study showed that Jangwonhwan at 400 mg/kg/day notably reduced Abeta (1-42) levels and beta-amyloid deposition and partially suppressed oxidative stress accumulation in SH-SY5Y neuroblastoma cells [25].…”
Section: Moas Of the Extractmentioning
confidence: 89%
“…Researchers also showed that YZQXF ameliorated cognitive decline by decreasing BDNF, TrkB, TNFα, IL-2, and IL-6 levels and upregulating acetylcholine and IL-10, thus promoting the activation of Erk and Akt signaling in APP/PS1 mice [23]. In an in vivo model of AD, SMYZD at concentrations of 11.88 g/kg/d can significantly improve memory abilities associated with an increase in the levels of NG2 and Ang1 protein expression levels in Wistar rats [22]. An in vitro study showed that Jangwonhwan at 400 mg/kg/day notably reduced Abeta (1-42) levels and beta-amyloid deposition and partially suppressed oxidative stress accumulation in SH-SY5Y neuroblastoma cells [25].…”
Section: Moas Of the Extractmentioning
confidence: 89%
“…Recently, many herbal plant extracts and natural compounds were screened for promoting neurogenesis, with some of them being promising drug candidates [25][26][27]. In China, a number of herb ingredients known from Traditional Chinese Medicine (TCM) have a long history of use for improved learning and memory [28][29][30]. Therefore, these medicinal herbs provide efficient resources for drug discovery to promote neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many herbal plant extracts and natural compounds were screened for promoting neurogenesis, with some of them being promising drug candidates [19,20]. In China, a number of herb ingredients known as Traditional Chinese Medicine (TCM) have a long history of use for improved learning and memory [21,22]. Therefore, these medicinal herbs provide efficient resources for drug discovery to promote neurogenesis.…”
Section: Discussionmentioning
confidence: 99%